Irrigation systems performance in Jordan - Shatanawi M.; Fardous A.; Mazahrih N.; Duqqah M. (Irrigation systems performance, 2005)
This paper discusses the performance of irrigation system in Jordan Rift Valley and the highlands where two criteria are considered. The first criteria implies the uniformity of water distribution in the irrigated field and the second concerned with water application efficiency. Diagnostic studies have shown that the overall efficiency in the JRV valley was about 65 percent considering conveyance and application efficiencies. The on-farm irrigation efficiency in the highlands using groundwater and micro irrigation has been measured to be 85 percent. The performance of the center pivot systems in the southern desert has given the uniformity of water application ranging from 76 to 84 percent under different operating pressures. Realizing the urgent need to control agricultural water demand, the Ministry of Water and irrigation and the Ministry of Agriculture have initiated several projects and programs. The paper discusses some of these initiatives such as the Irrigation Advisory Services, Kafa'a project and the Irrigation Information System. The aim of these programs is to increase efficiency of water use, improve irrigation management practices and up grade design and evaluation capabilities.
2. WASAMED Workshop: Irrigation Systems Performance, 2004/06/24-28, Hammamet (Tunisia)